Optimization of Piwulang Text Learning by Using Media of Powerquiz Game - Yudha Perdana, Vaundra; Suhita, Raheni; Saddhono, Kundharu; Devilito, Rio; Muflikh Raharjo, Yusuf; Wahyu Setyawan, Bagus; Anindyarini, Atikah; ., Sumarwati; Suhita, Damayanti; Aziz, Firman; Kustriyono, Erwan; Korniawan, Rostamaji; et al. (International Journal of Engineering and Technology, 2026)
Powerquiz game is a learning media based TI with the employment of Power Point application. This media can optimize Javanese learning, especially basic competency of piwulang text. This study aims to describe (1) feasibility of powerquiz game in optimizing piwulang text learning, and (2) evaluation responses of expert in learning material, expert in learning media, Javanese teacher and responses of junior high school students at eight grade toward powerquiz game usage in teaching and learning process. The method was R&D (Research and Development). Sources of data included 100 students, expert in TI, teachers and document. The data obtained were analyzed through descriptive qualitative and quantitative analysis to describe and to explain the feasibility of powerquiz game for piwulang text learning on junior high school students at eight grade. The result shows that: (1) powerquiz game can optimize piwulang text learning, and (2) powerquiz game usage get positive responses from expert in learning material with average score of 89.7, categorized as a very good score; expert in learning media with average score of 89.5, categorized as a very good score; Javanese teachers with average score of 96.6, categorized as a very good score.